Cellular cytotoxicity is a form of immunogenic cell death - Minute, Luna (J Immunother Cancer, 2020)
BACKGROUND: The immune response to cancer is often conceptualized with the cancer immunity cycle. An essential step in this interpretation is that antigens released by dying tumors are presented by dendritic cells to naive or memory T cells in the tumor-draining lymph nodes. Whether tumor cell death resulting from cytotoxicity, as mediated by T cells or natural killer (NK) lymphocytes, is actually immunogenic currently remains unknown. METHODS: In this study, tumor cells were killed by antigen-specific T-cell receptor (TCR) transgenic CD8 T cells or activated NK cells. Immunogenic cell death was studied analyzing the membrane exposure of calreticulin and the release of high mobility group box 1 (HMGB1) by the dying tumor cells. Furthermore, the potential immunogenicity of the tumor cell debris was evaluated in immunocompetent mice challenged with an unrelated tumor sharing only one tumor-associated antigen and by class I major histocompatibility complex (MHC)-multimer stainings. Mice deficient in Batf3, Ifnar1 and Sting1 were used to study mechanistic requirements. RESULTS: We observe in cocultures of tumor cells and effector cytotoxic cells, the presence of markers of immunogenic cell death such as calreticulin exposure and soluble HMGB1 protein. Ovalbumin (OVA)-transfected MC38 colon cancer cells, exogenously pulsed to present the gp100 epitope are killed in culture by mouse gp100-specific TCR transgenic CD8 T cells. Immunization of mice with the resulting destroyed cells induces epitope spreading as observed by detection of OVA-specific T cells by MHC multimer staining and rejection of OVA(+) EG7 lymphoma cells. Similar results were observed in mice immunized with cell debris generated by NK-cell mediated cytotoxicity. Mice deficient in Batf3-dependent dendritic cells (conventional dendritic cells type 1, cDC1) fail to develop an anti-OVA response when immunized with tumor cells killed by cytotoxic lymphocytes. In line with this, cultured cDC1 dendritic cells uptake and can readily cross-present antigen from cytotoxicity-killed tumor cells to cognate CD8(+) T lymphocytes. CONCLUSION: These results support that an ongoing cytotoxic antitumor immune response can lead to immunogenic tumor cell death.